Religious Minorities and the Indonesian Judiciary: Legal Protection or Institutionalized Discrimination? (Indonesian Court and Justice Review, 2025)
Indonesia’s constitutional commitment to religious freedom often stands in contrast to the lived experiences of religious minorities, particularly in the context of judicial processes. This study critically examines how the Indonesian judiciary has handled cases involving religious minority groups, focusing on whether the courts serve as protectors of minority rights or inadvertently reinforce systemic discrimination. Through an analysis of key court decisions, including blasphemy cases and disputes over places of worship, the research explores legal reasoning, procedural fairness, and alignment with international human rights standards. Findings reveal a pattern in which the judiciary, under pressure from dominant social and political forces, frequently prioritizes public order over the protection of minority rights. Legal provisions such as the Blasphemy Law (UU No. 1/PNPS/1965) are often applied broadly, enabling selective prosecution and legitimizing societal intolerance. While some rulings affirm constitutional guarantees, inconsistent application of the law undermines trust in the judiciary's impartiality. The novelty of this study lies in its empirical and doctrinal analysis of judicial treatment of religious minorities, highlighting institutional and normative challenges. This research contributes to debates on religious pluralism, constitutionalism, and the role of courts in protecting vulnerable populations in a plural society.